Impact of Time Interval between Radiation and Free Autologous Breast Reconstruction - Mull, Aaron B.; Qureshi, Ali A.; Zubovic, Ema; Rao, Yuan J.; Zoberi, Imran; Sharma, Ketan; Myckatyn, Terence M. (Journal of Reconstructive Microsurgery, 2017)
Background To evaluate whether the timing of surgery after radiation in autologous breast reconstruction affects major complications.Methods We performed a retrospective review of 454 free flaps (331 patients) for breast reconstruction at a single institution from 2003 to 2014. Charts were reviewed for age, BMI, laterality, flap type (TRAM, msTRAM, DIEP), surgeon, donor vessels (IMA, TD), chemotherapy, smoking, diabetes, hypertension, DVT, venous anastomoses, vein size, and time from radiation (none, < 12 months, or ≥ 12 months). The primary outcome of major complications was defined as partial/total flap loss, thrombosis, ischemia, or hematoma requiring return to the operating room. To identify independent predictors of major complications, a multivariate logistic regression was constructed. Alpha = 0.05 indicated significance in all tests.Results Average age was 47.4 ± 8.4. Free flaps consisted of msTRAM (41.1%), TRAM (29.6%), or DIEP (29.3%). The donor vessel was IMA in 66.9% of flaps or TD in 33.0% of patients with 90.7% using only one vein and 9.3% with two veins. The average IMA/TDV size was 2.5 cm ± 0.5. Preoperative radiation occurred in 31.2% of flaps. There were 54 flaps with at least one major complication (11.7%). On multivariate regression, only flap type (OR =4.04, p < .01) and vein size (OR = 0.13, p = 0.02) independently predicted major complications.Conclusion There was no significant difference in major complications between flaps who had reconstruction within 12 months and greater than 12 months after radiation. Only having a more muscle sparing technique or smaller vein size were independent risk factors for major complications.
Keywords: radiation; free flap; autologous breast reconstruction